(untitled) (Journal of Management and Educational Sciences, 2024)
The main purpose of this study is to measure the perceptions of school principals’ leadership behavior and classroom management skill levels according to teachers’ opinions, to examine the possible relationship between them and to determine significant differences in terms of demographic variables. The research was carried out with the relational screening model. According to the results of the research; it was revealed that teachers’ perceptions of school principal leadership behavior and classroom management skills were above average. In addition, it was revealed that teachers’ perceptions of classroom management skills and school principal leadership behaviors did not change according to women and men; married and single; undergraduate and graduate. In the examination according to age; in the classroom management skills of teachers between the ages of 31-40, 41-50 and 51 and above, the perception of classroom management skills was higher than the 20-30 age group. In the examination according to professional experience status; in the dimension of teachers’ classroom management skills; the perception of classroom management skills of the 21-30 year group was higher than the 1-10 year and 11-20 year professional experience groups. Finally, there is a low-level positive relationship between the teachers within the scope of the research’s school principal leadership behaviors and teachers’ classroom management skills. In addition, it is understood that teachers’ perceptions of school principal leadership behaviors significantly positively predict teachers’ perceptions of classroom management skills. In other words, a 100-unit increase in the school principal leadership behaviors dimension increases teachers’ perceptions of classroom management skills by 26.4%.